2008
DOI: 10.1111/j.1467-9868.2008.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Sparse Generalized Longitudinal Observations with Latent Gaussian Processes

Abstract: In longitudinal data analysis one frequently encounters non-Gaussian data that are repeatedly collected for a sample of individuals over time. The repeated observations could be binomial, Poisson or of another discrete type or could be continuous. The timings of the repeated measurements are often sparse and irregular. We introduce a latent Gaussian process model for such data, establishing a connection to functional data analysis. The functional methods proposed are non-parametric and computationally straight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
166
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 30 publications
1
166
0
Order By: Relevance
“…Our approach can be seen as an extension of functional principal component analysis for multilevel functional data [7]. Our methods apply to longitudinal data where each observation is functional, and should thus not be confused with nonparametric methods for the longitudinal profiles of scalar variables [17,30,31,37,41,48,50,51]. For good introductions to functional data analysis in general, please see [10,34].…”
Section: Introductionmentioning
confidence: 99%
“…Our approach can be seen as an extension of functional principal component analysis for multilevel functional data [7]. Our methods apply to longitudinal data where each observation is functional, and should thus not be confused with nonparametric methods for the longitudinal profiles of scalar variables [17,30,31,37,41,48,50,51]. For good introductions to functional data analysis in general, please see [10,34].…”
Section: Introductionmentioning
confidence: 99%
“…As has been demonstrated in various settings (James et al 2000;Yao et al 2005a;Hall et al 2008), the FDA paradigm to extend classical statistical methodology to the case of functional data can be worked out even when one has available only sparse and irregularly spaced measurements for each subject or item in the sample. A topic that has been of much interest lately is modeling variation in time in addition to variation in amplitude.…”
Section: Brief Overview On Selected Topics In Functional Data Analysismentioning
confidence: 99%
“…Nevertheless, based on our experience and the study in Lin and Carroll (2000), it is suggested to ignore the withinsubject correlation in conjunction with cross-validation type search, at least when the measurements are sparsely observed with noise. The issue with the non-negative definiteness of the covariance estimation is less pronounced in our implementation of PACE algorithm, as we followed the suggestion made in Hall et al (2008) to discard the basis associated with negative eigenvalues. It has been shown theoretically that this amendment leads to asymptotically negligible impact on the resulting covariance estimator.…”
Section: Implementation and Numerical Examplesmentioning
confidence: 99%